The E3 ubiquitin ligase Itch limits the progression of post-traumatic osteoarthritis in mice by inhibiting macrophage polarization. Issue 8 (August 2021) - Lin, X.; Wang, W.; McDavid, A.; Xu, H.; Boyce, B.F.; Xing, L.
Summary: Objective: Osteoarthritis (OA) is characterized by articular cartilage loss, associated with synovial inflammation. We recently reported increased pro-inflammatory macrophages in murine post-traumatic OA (PTOA) joints, and blockade of the ubiquitin-proteasome system alleviates PTOA progression. However, the mechanisms whereby protein ubiquitination influences PTOA pathology are not well studied. We hypothesized that loss of the negative regulator of inflammation, E3 ligase Itch, in macrophages contributes to joint OA tissue damage by promoting pro-inflammatory polarization of macrophages. Methods: Mice deficient Itch in macrophages ( M Δ Itch ) were generated by crossing Itch fl/fl mice with LysM-Cre mice. PTOA surgery was performed on global Itch knockout, Itch −/−, mice and M Δ Itch mice. Joint tissue damage and synovial macrophages were examined. Itch −/− cells were treated with IL-1 and pro-inflammatory polarization was determined. Expression of Itch protein and mRNA in PTOA synovium were assessed at different time points post PTOA. Results: Similar to Itch −/− mice, M Δ Itch mice developed more severe joint damage than control mice following PTOA surgery (mean difference of OARSI score: 1.17 (95% CI 0.31–2.03) between M Δ Itch and Itch fl/fl mice), accompanied by increased the inflammatory macrophage infiltration in the synovium (mean difference of % F4/80 + CD86 + CD36-inflammatory macrophages: 14.81 (95% CI 8.90–20.73) between M Δ Itch and Itch fl/fl mice). Itch −/− macrophages exerted pro-inflammatory phenotype in response to IL-1β treatment. Itch protein, but not mRNA levels decreased during PTOA progression. Conclusion: The negative regulator of inflammation, Itch, limits PTOA progression by inhibiting macrophage pro-inflammatory polarization. Itch protein degradation may contribute to PTOA pathology.